ACT UP Milwaukee Records: Text Corpus of AV Materials - (:unkn) unknown (My University, 2021)
The ACT UP Milwaukee Collection documents the history and activism of the Milwaukee chapter of ACT UP (AIDS Coalition to Unleash Power). This text corpus was derived from audio recordings in the collection documenting ACT UP demonstrations, AIDS Activist TV, and the Brand New Queer Program. The full finding aid for the ACT UP Milwaukee Records is found here: http://digital.library.wisc.edu/1711.dl/wiarchives.uw-mil-uwmmss0203